"Suffering is Not Pain" by Paul Ricœur - Astrid Chevance; Luz Ascarate (Études Ricoeuriennes / Ricoeur Studies)
In 1992, Ricœur delivered his lecture, "Suffering is Not Pain," at a psychiatry colloquium, addressing clinicians eager to explore this profound human experience, which is notably absent from the traditional psychiatric corpus. Ricœur examined the semiology of suffering through three moments: the specific relationship between oneself and the other, the characterization of a diminution in the power to act, and, finally, a hermeneutic reflection on suffering as an enigma that has something to teach—both at the level of self-reflection on one’s own existence and in the context of relationships with others. It thus appears that suffering can open the way to a hermeneutic of the symbols of human existence, whose meaningful manifestations can also be clinical. However, this text does not belong to Ricœur’s systematic work. To understand its significance this annotated translation accompanied by its explanatory introduction, allows for a detailed reading that considers the intertextual references and the meanings implied by Ricœur’s expressions. By integrating clinical and philosophical language, this translation acknowledges the importance of multi- and interdisciplinary approaches to the study of suffering.